2017
DOI: 10.1038/ncb3631
|View full text |Cite
|
Sign up to set email alerts
|

Class III phosphatidylinositol-3-OH kinase controls epithelial integrity through endosomal LKB1 regulation

Abstract: The molecular mechanisms underlying the interdependence between intracellular trafficking and epithelial cell polarity are poorly understood. Here we show that inactivation of class III phosphatidylinositol-3-OH kinase (CIII-PI3K), which produces phosphatidylinositol-3-phosphate (PtdIns3P) on endosomes, disrupts epithelial organization. This is caused by dysregulation of endosomally localized Liver Kinase B1 (LKB1, also known as STK11), which shows delocalized and increased activity accompanied by dysplasia-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 106 publications
1
22
0
Order By: Relevance
“…Another kinase regulated by Vps34 is the endosomally-localized pool of LKB1 kinase, an activator of AMPK and a regulator of cell polarity 221 . This polarity function of LKB1 depends on its binding to the endosomally-localised WDFY2, a FYVE domain-containing protein, and the transit of LKB1 from Rab5to Rab7-positive compartments during endosomal maturation.…”
Section: Regulation Of Protein Kinase Signalling By Vps34 Like the Cmentioning
confidence: 99%
“…Another kinase regulated by Vps34 is the endosomally-localized pool of LKB1 kinase, an activator of AMPK and a regulator of cell polarity 221 . This polarity function of LKB1 depends on its binding to the endosomally-localised WDFY2, a FYVE domain-containing protein, and the transit of LKB1 from Rab5to Rab7-positive compartments during endosomal maturation.…”
Section: Regulation Of Protein Kinase Signalling By Vps34 Like the Cmentioning
confidence: 99%
“…We favor instead the hypothesis of TSHR mistrafficking into intracellular vesicles. Recent work in Drosophila revealed that Vps34 inactivation or pharmacological inhibition using the small molecule inhibitor SAR405 causes alteration of cell polarity and disruption of epithelial architecture by relieving LKB1 inhibition and triggering JNK activation (14). A role of Vps34 in epithelial organization and polarity was also observed in 3D cultures of Caco-2 kidney cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in Drosophila revealed that Vps34 inactivation or pharmacological inhibition using the small molecule inhibitor SAR405 causes alteration of cell polarity and disruption of epithelial architecture by relieving LKB1 inhibition and triggering JNK activation (14). A role of Vps34 in epithelial organization and polarity was also observed in 3D cultures of Caco-2 kidney cells (14). It would be interesting to analyze the activation states of LKB1 and JNK in Vps34 cKO thyroid tissue, and, if modified, to cross Vps34 cKO with floxed LKB1 alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4A, B). We performed a similar experiment also in IRSp53-KO Caco-2 cells by monitoring the distribution of aPKC, which is the most commonly-used apical marker in this in for the distribution of aPKC 28,30,31 . Likewise in MDCK cells, IRSp53 depletion resulted in formation of aPKC multi-foci at the 3-4-cell stage during cystogenesis, as compared to the control Caco-2 cells ( Supplementary Fig.…”
Section: Irsp53 Controls the Distribution And Trafficking Of The Apicmentioning
confidence: 99%